Determinants of Loan Repayment: The Case of Microfinance Institutions in Nepal - Duwal, Bal Ram; Thapa, Bharat Singh (Nepal Journal of Multidisciplinary Research, 2025)
Background Loan delinquency among microfinance borrowers is a growing global concern, especially in South Asia, where microfinance programs have shown inconsistent performance. In Nepal, 59 microfinance institutions (MFIs) report a bad debt rate of 4.68% and an average non-performing loan (NPL) ratio of 7.49%. Timely repayment is critical to the financial sustainability of MFIs, yet there is limited research on the factors influencing repayment behaviour in Nepal. Objective This study aims to examine the determinants of loan repayment behaviour among MFI borrowers in Nepal, focusing on socio-demographic characteristics of borrowers, business-related attributes, and lender-specific factors. Methods Data were collected through a survey of 384 purposively selected borrowers in Chitwan district, the third largest microfinance hub in Nepal. Multiple regression analysis was used to evaluate the impact of these factors on repayment performance. Diagnostic tests confirmed the absence of multicollinearity. Findings Borrower socio-demographic characteristics had the strongest positive influence on repayment, with female gender, higher education, and financial literacy emerging as significant predictors. Business-related factors such as higher transaction volumes, full loan utilization, and involvement in non-agricultural enterprises also positively affected repayment, though business profitability was not significant. Among lender characteristics, friendly loan policies, feasible repayment schedules, and clear communication of loan terms improved repayment, while intensive supervision had a negative effect. Implication MFIs should prioritize careful borrower selection, promote entrepreneurship development for high-risk agricultural borrowers, and strengthen staff advisory and communication skills. Implementing flexible, borrower-friendly loan policies tailored to clients’ conditions can further enhance repayment. The study enhances understanding of repayment behaviour in Nepalese microfinance and offers practical recommendations for improving MFI sustainability.